1990
DOI: 10.1177/000348949009900610
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography of the Inferior Constrictor and Cricopharyngeal Muscles during Swallowing

Abstract: Electromyography (EMG) of the inferior pharyngeal constrictor (IC) and the cricopharyngeal (CP) muscle was recorded in 18 patients with swallowing and/or aspiration problems who were candidates for cricopharyngeal myotomy. The EMG recordings were compared to those of 13 "normal" subjects who did not suffer from such problems. Differences in EMG activity between the control group and the patient group were considered with respect to the clinical symptoms in the patient group. Recording of EMG in the CP and IC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…The caudal NMC of the IPC and the cricopharyngeus muscle are located below the opening of the larynx, and their continuous closure could prevent air from entering the esophagus during inspiration. The large population of fast-twitch fibers in the rostral NMC of the IPC could be responsible mainly for the rapid and forceful contraction during swallowing, as demonstrated by electrophysiological studies (Basmajian and Dutta, 1961a;Elidan et al, 1990).…”
Section: Nmcs Within the Human Ipc Musclementioning
confidence: 98%
See 2 more Smart Citations
“…The caudal NMC of the IPC and the cricopharyngeus muscle are located below the opening of the larynx, and their continuous closure could prevent air from entering the esophagus during inspiration. The large population of fast-twitch fibers in the rostral NMC of the IPC could be responsible mainly for the rapid and forceful contraction during swallowing, as demonstrated by electrophysiological studies (Basmajian and Dutta, 1961a;Elidan et al, 1990).…”
Section: Nmcs Within the Human Ipc Musclementioning
confidence: 98%
“…It is well recognized that the IPC plays an important role in upper-airway functions during swallowing (Basmajian and Dutta, 1961a;Kawasaki et al, 1964;Elidan et al, 1990), respiration (Rowe et al, 1984;Sherrey et al, 1986;Praud et al, 1996;O'Halloran et al, 1999;Feroah et al, 2000), and voice production (Ueda et al, 1972;Shin et al, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(J Histochem Cytochem 55:199-207, 2007) K E Y W O R D S upper esophageal sphincter cricopharyngeus muscle inferior pharyngeal constrictor upper esophagus fiber types myosin heavy chain isoforms immunocytochemistry immunoblotting swallowing UPPER ESOPHAGEAL SPHINCTER (UES) is a functional entity composed of the cricopharyngeus (CP), the most inferior part of the inferior pharyngeal constrictor (iIPC), and the upper esophagus (UE) (for review, see Sanders 2001,2002). Normally, the UES is collapsed and exhibits sustained muscle activity in the resting state (Elidan et al 1990;Lang et al 1991); it only relaxes and opens during swallowing, vomiting, and belching (Kahrilas et al 1986;Elidan et al 1990;Lang et al 1991Lang et al ,1993. The UES has many unique characteristics including tonic activity, high degree of elasticity, and predominant slow-twitch fibers.…”
Section: S U M M a R Ymentioning
confidence: 99%
“…However, the functional implications of both fiber layers in the UES remain unknown. Previous electromyographic (EMG) studies demonstrated that the UES is active during swallowing (Shipp et al 1970;Elidan et al 1990), respiration (Kawasaki and Takenouchi 1964), and speech (Baer et al 1976). Unfortunately, no studies were designed to perform EMG recordings from each of the fiber layers.…”
Section: The Journal Of Histochemistry and Cytochemistrymentioning
confidence: 99%